EXAMINING THE IMPACT OF SHORT-FORM CONTENT MARKETING ON CUSTOMER SATISFACTION AND LOYALTY - Angelia, Ivana (GEMAH RIPAH: Jurnal Bisnis, 2025)
This study examines the influence of short-form content marketing on customer satisfaction and loyalty, with a specific focus on the mediating role of satisfaction. Utilizing a quantitative approach, the research employs a causal explanatory design with a sample of 81 undergraduate students from Institut Teknologi dan Bisnis Sabda Setia who actively engage with short-form video content on social media. Data were collected using a structured questionnaire and analyzed through multiple regression and mediation analysis using SPSS and SmartPLS. The findings reveal that short-form content significantly and positively affects customer satisfaction. Furthermore, customer satisfaction has a positive influence on customer loyalty and mediates the relationship between short-form content and loyalty. However, a surprising result emerged: short-form content exhibits a negative direct effect on customer loyalty. This suggests that while such content may foster satisfaction, it does not independently promote loyalty without satisfaction acting as an intermediary. The results emphasize the importance of content quality and meaningful customer experiences in sustaining loyalty in digital marketing. Therefore, marketers should not rely solely on short-form content to drive loyalty but should focus on enhancing overall customer satisfaction as a strategic pathway.